WAVELET ANALYSIS OF THERMAL WAVE PROPAGATION IN NON-UNIFORM REINFORCED COMPOSITES - Писаренко, Олександр (SWorldJournal, 2024)
The goal of this work was to build a software model that allows one to detect the local location of inclusions in the volume of a reinforced composite. The numerical model included blocks for statistical processing of synchronous infrared thermography dat